Pengaruh Rasio Pembayaran Dividen terhadap Harga Saham PT Bukit Asam (Persero) Tbk Periode 2005-2015 (Jurnal Manajemen dan Organisasi, 2017)
PT Bukit Asam (Persero) Tbk (PTBA) is a large company engaged in the sub-sector of coal mining and has been listed in the Indonesia Stock Exchange (IDX) as a public company and was registered to have an Initial Public Offering (IPO) in year 2002. The investors as shareholders will strongly expect a high dividend every year (% per year). The annual dividend (in %) so called as Dividend payout ratio (DPR). The objective of the research are to analyze the effect of the DPR on stock prices of PTBA in the period 2005-2015 and as reference to determine dividend policy. The research secondary data was obtained from BEI, Indonesian Central Securities Depository PTBA. The simple linear regression model was developed in the research where the DPR stands for independent variable (y) and the dayly average stock price from the declaration dateto cum date stands for dependent variables. The results showed a positive relationship and unreal 42,3% between the DPR and the stock price of PTBA with the influence of 18,6%. But both variables do not have a linear relationship, so as to predict the stock price can not be done simply by using DPR as independent variables, but also need to consider other factors.